Analisis Determinan Perilaku Pencegahan HIV/AIDS pada Remaja - Sukarni Setya Yuningsih; Eva Berliana; Giati Giati (Universitas Malahayati Lampung, 2026)
ABSTRACT HIV/AIDS remains a global public health issue, including in Indonesia. Adolescents are a group vulnerable to risk behaviors that can increase HIV/AIDS transmission. HIV/AIDS prevention behaviors are influenced by various factors, such as knowledge, attitudes, peer influence, family support, social media exposure, and the role of teachers. To analyze the determinants associated with HIV/AIDS prevention behaviors among adolescents. This quantitative study with a cross-sectional design was conducted among students at SMK Yasmida Ambarawa (Pringsewu Regency) and SMKN Gunung Pelindung (East Lampung). The sample consisted of 140 respondents selected using purposive sampling. Data were collected using a questionnaire tested for validity and reliability, then analyzed via univariate and bivariate methods using the Chi-Square test with a significance level of α = 0.05. At SMK Yasmida Ambarawa, the majority of respondents demonstrated good HIV/AIDS prevention behaviors (67.1%), good knowledge (68.6%), positive attitudes (78.6%), and positive peer influence (74.3%). Significant associations were found between HIV/AIDS prevention behaviors and knowledge (p=0.001), attitudes (p=0.005), and peer influence (p=0.001). At SMKN Gunung Pelindung, the majority of respondents demonstrated good HIV/AIDS prevention behaviors (61.4%), supportive family support (74.3%), high social media exposure (71.4%), and a good role of teachers (67.1%). Significant associations were found between HIV/AIDS prevention behaviors and family support (p=0.003), social media exposure (p=0.002), and the role of teachers (p=0.003). Knowledge, attitudes, peer influence, family support, social media exposure, and the role of teachers are significantly associated with HIV/AIDS prevention behaviors among adolescents. Schools and healthcare workers are advised to enhance HIV/AIDS prevention education on an ongoing basis by involving families and peers. Keywords: HIV/AIDS, Prevention Behavior, Adolescents, Knowledge, Attitudes, Peers, Family Support, Role of Social Media, Role of Teachers. ABSTRAK HIV/AIDS masih menjadi masalah kesehatan masyarakat di dunia, termasuk di Indonesia. Remaja merupakan kelompok yang rentan terhadap perilaku berisiko yang dapat meningkatkan penularan HIV/AIDS. Perilaku pencegahan HIV/AIDS dipengaruhi oleh berbagai faktor, seperti pengetahuan, sikap, pengaruh teman sebaya, dukungan keluarga, paparan media sosial, dan peran guru. Menganalisis determinan yang berhubungan dengan perilaku pencegahan HIV/AIDS pada remaja. Penelitian kuantitatif dengan desain cross-sectional ini dilakukan pada siswa SMK Yasmida Ambarawa Kabupaten Pringsewu dan SMKN Gunung Pelindung Lampung Timur. Sampel berjumlah 140 responden yang dipilih menggunakan purposive sampling. Data dikumpulkan menggunakan kuesioner yang telah diuji validitas dan reliabilitas, kemudian dianalisis secara univariat dan bivariat menggunakan uji Chi-Square dengan tingkat kemaknaan α = 0,05. Di SMK Yasmida Ambarawa, sebagian besar responden memiliki perilaku pencegahan HIV/AIDS baik (67,1%), pengetahuan baik (68,6%), sikap positif (78,6%), dan pengaruh teman sebaya baik (74,3%). Terdapat hubungan antara pengetahuan (p=0,001), sikap (p=0,005), dan pengaruh teman sebaya (p=0,001) dengan perilaku pencegahan HIV/AIDS. Di SMKN Gunung Pelindung, sebagian besar responden memiliki perilaku pencegahan HIV/AIDS baik (61,4%), dukungan keluarga mendukung (74,3%), paparan media sosial tinggi (71,4%), dan peran guru baik (67,1%). Terdapat hubungan antara dukungan keluarga (p=0,003), paparan media sosial (p=0,002), dan peran guru (p=0,003) dengan perilaku pencegahan HIV/AIDS. Pengetahuan, sikap, pengaruh teman sebaya, dukungan keluarga, paparan media sosial, dan peran guru berhubungan signifikan dengan perilaku pencegahan HIV/AIDS pada remaja. Disarankan kepada sekolah dan tenaga kesehatan untuk meningkatkan edukasi pencegahan HIV/AIDS secara berkelanjutan dengan melibatkan keluarga dan teman sebaya. Kata Kunci: HIV/AIDS, Perilaku Pencegahan, Remaja, Pengetahuan, Sikap, Teman Sebaya, Dukungan Keluarga, Peran Media Sosial, Peran Guru.